A framework for applying critical success factors to ERP implementation projects. (1st January 2014) - Gupta, Rekha; Naqvi, S. Kazim
Enterprise resource planning (ERP) system is a tool to integrate the departments and functions across an organisation to help achieve its specific business goals and objectives. The complex and integrated nature of ERP system is often coupled with time constraints and substantial financial commitments that inevitably make its implementation to be a highly risky undertaking with an inherent high failure probability. Reviews of the existing literature on the subject suggest that critical success factors (CSFs) have been studied by researchers for risk aversion in ERP implementations. However, with no suggested methods or framework for monitor and control coupled with the inherent subjectivity, CSFs studies for ERP implementation find little practical usage. This paper proposes a framework for applying the earlier cited CSFs studies for ERP systems with particular emphasis on bringing objectivity leading to their effective monitoring and control. The paper also attempts to highlight the short-comings of existing CSFs studies based on the proposed framework.